Personality and behavioural syndromes in two species of fruit bats (Chiroptera: Phyllostomidae) - Miguel, Pedro Henrique [UNESP] (2024)
Personality indicates consistency in individual behavioural responses across time, and different personality traits may be correlated in behavioural syndromes. Investigating such dimensions of the behaviour in frugivorous animals is crucial given the potential link between individual variation and their ecological significance as seed dispersers. However, few studies have explored the existence of personality traits and behavioural syndromes in fruit bats. In this context, we aimed to test whether the Neotropical fruit bats Artibeus lituratus and Carollia perspicillata show individual repeatability (i.e. personality) related to activity, docility and boldness and, if so, whether correlations between these personality axes constitute behavioural syndromes. All tests were repeated after 48 h to analyse repeatability. We found high individual repeatability in aggressiveness, activity and boldness for both species, but different behavioural syndromes for each species. For C. perspicillata, the three behaviours were correlated, with the least docile individuals being bolder and more active. For A. lituratus, docility and boldness were positively correlated but activity was not correlated with docility or boldness. Considering these different syndromes, our results suggest that C. perspicillata may show reduced variation in behavioural profiles compared to A. lituratus, likely influenced by species-specific selective pressures. Although our results are restricted to males, the existence of behavioural syndromes in these frugivorous bats contributes to our understanding of the importance of individual variation in behaviour on the ecological functions of these seed dispersers.